2021
DOI: 10.3390/biom11081132
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Long Non-Coding RNAs and MicroRNAs in Neurodegenerative Diseases: A Perspective of Machine Learning

Abstract: Neurodegenerative diseases (NDs) are characterized by progressive neuronal dysfunction and death of brain cells population. As the early manifestations of NDs are similar, their symptoms are difficult to distinguish, making the timely detection and discrimination of each neurodegenerative disorder a priority. Several investigations have revealed the importance of microRNAs and long non-coding RNAs in neurodevelopment, brain function, maturation, and neuronal activity, as well as its dysregulation involved in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 250 publications
(204 reference statements)
0
10
0
Order By: Relevance
“…On the contrary, this study was limited to protein coding genes and future work should include similar analyses on noncoding RNA (ncRNA) expression, such as microRNAs and long noncoding RNAs, as previous studies have shown that such RNAs are expressed in a tissue- and cell-specific manner, involved in neuronal differentiation and function, and implicated in various brain disorders. 88 - 95 However, although databases providing information on ncRNAs along with tissue expression profiles and predicted functions are now available as well as ncRNA knockout mouse models with reported phenotypes, 96 - 101 there is still a lack of databases that compiles the results from mutational studies and which also links the ncRNAs to phenotype in a similar way as the MGI’s Mammalian Phenotype database. Such databases would be of high value when further studying the roles of hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, this study was limited to protein coding genes and future work should include similar analyses on noncoding RNA (ncRNA) expression, such as microRNAs and long noncoding RNAs, as previous studies have shown that such RNAs are expressed in a tissue- and cell-specific manner, involved in neuronal differentiation and function, and implicated in various brain disorders. 88 - 95 However, although databases providing information on ncRNAs along with tissue expression profiles and predicted functions are now available as well as ncRNA knockout mouse models with reported phenotypes, 96 - 101 there is still a lack of databases that compiles the results from mutational studies and which also links the ncRNAs to phenotype in a similar way as the MGI’s Mammalian Phenotype database. Such databases would be of high value when further studying the roles of hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…These signs are related to the loss of dopaminergic neurons in the substantia nigra and the pathology spreading to other regions of the brain. The α-synuclein protein elicits the insoluble aggregates that compose the main structure of Lewy bodies leading to the death of dopaminergic neurons [ 90 ]. miR-7 inhibits α-synuclein expression directly through the 3′ UTR of α-synuclein mRNA.…”
Section: Micrornasmentioning
confidence: 99%
“…Both the regulation of genes controlled by miRNAs and altered miRNA expression have been linked to several neurodegenerative diseases (NDs) such as Alzheimer's disease and Parkinson's disease. In the context of these two diseases, studies using blood samples and postmortem brain tissue from patients have highlighted differential expression of miRNAs such as mir-1, mir-22p, mir-26b -3p, and mir-28-3p (Pritchard et al, 2012;Hu et al, 2016;Kumar et al, 2017;Garcia-Fonseca et al, 2021). Several studies also linked Huntington's disease (HD) pathogenesis to miRNA regulation (Marti et al, 2010;Ghose et al, 2011;Jin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These methods can be divided into two main classes of algorithms: supervised learning algorithms and unsupervised learning algorithms. The former class involves feeding the algorithm with labeled data that, after training, enable unknown information to be labeled based on the patterns learned from the data used for training, namely the training set, whereas the purpose of the latter class is to classify the data, based on similar patterns in the data itself (Carpenter and Huang, 2018;Garcia-Fonseca et al, 2021).…”
Section: Introductionmentioning
confidence: 99%